Repurposing the Killing Machine: Non-canonical Roles of the Cell Death Apparatus in Caenorhabditis elegans Neurons - Juanez, Karen; Ghose, Piya (Frontiers in Cell and Developmental Biology, 2022)
Abstract Here we highlight the increasingly divergent functions of the Caenorhabditis elegans cell elimination genes in the nervous system, beyond their well-documented roles in cell dismantling and removal. We describe relevant background on the C. elegans nervous system together with the apoptotic cell death and engulfment pathways, highlighting pioneering work in C. elegans. We discuss in detail the unexpected, atypical roles of cell elimination genes in various aspects of neuronal development, response and function. This includes the regulation of cell division, pruning, axon regeneration, and behavioral outputs. We share our outlook on expanding our thinking as to what cell elimination genes can do and noting their versatility. We speculate on the existence of novel genes downstream and upstream of the canonical cell death pathways relevant to neuronal biology. We also propose future directions emphasizing the exploration of the roles of cell death genes in pruning and guidance during embryonic development.